ปัจจัยที่มีความสัมพันธ์กับกระบวนการจัดการความรู้ของสถาบันทันตกรรม กรมการแพทย์ กระทรวงสาธารณสุข - ขอพรกลาง อภิญญา; เตชาทวีวรรณ แววตา; ศราวณะวงศ์ จุฑารัตน์ (บรรณศาสตร์ มศว, 2018)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาระดับปฏิบัติตามกระบวนการจัดการความรู้ปัจจัยด้านบุคลากรและปัจจัยด้านองค์กรที่มีความสัมพันธ์กับกระบวนการจัดการความรู้ของสถาบันทันตกรรม กรมการแพทย์ กระทรวงสาธารณสุข ใช้วิธีวิจัยเชิงปริมาณศึกษาจากกลุ่มตัวอย่าง ได้แก่ บุคลากรสถาบันทันตกรรม จำนวน 124 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติสำหรับทดสอบสมมติฐานการวิจัย ได้แก่ การวิเคราะห์ค่าสหสัมพันธ์แบบเพียร์สัน พบผลการวิจัย ดังนี้ 1. สถาบันทันตกรรมมีการปฏิบัติตามกระบวนการจัดการความรู้ โดยรวมอยู่ในระดับปานกลาง เมื่อพิจารณารายด้าน พบว่า ทุกกระบวนการมีการปฏิบัติในระดับปานกลาง ด้านที่มีค่าเฉลี่ยสูงสุด คือ การใช้ความรู้ รองลงมา คือ การถ่ายทอดความรู้ การสร้างและแสวงหาความรู้ และการจัดระบบความรู้ ตามลำดับ 2.ปัจจัยด้านบุคลากรที่มีความสัมพันธ์กับกระบวนการจัดการความรู้ของสถาบันทันตกรรม โดยรวมค่าเฉลี่ยอยู่ในระดับมาก เมื่อพิจารณารายด้าน พบว่า ปัจจัยที่ค่าเฉลี่ยสูงสุดและอยู่ในระดับมาก คือ แรงจูงใจใฝ่สัมฤทธิ์ และการเรียนรู้ด้วยตนเอง ส่วนปัจจัยที่มีค่าเฉลี่ยอยู่ในระดับปานกลาง คือ การเสริมพลังอำนาจในงาน นอกจากนี้ปัจจัยด้านบุคลากรมีความสัมพันธ์กับกระบวนการจัดการความรู้ของสถาบันทันตกรรมทั้ง 4 กระบวนการ โดยมีความสัมพันธ์เชิงบวกในระดับปานกลาง 3. ปัจจัยด้านองค์กรที่มีความสัมพันธ์กับกระบวนการจัดการความรู้ของสถาบันทันตกรรม โดยรวมค่าเฉลี่ยอยู่ในระดับปานกลาง เมื่อพิจารณารายด้าน พบว่า ทุกปัจจัยมีค่าเฉลี่ยอยู่ในระดับปานกลาง ปัจจัยที่ค่าเฉลี่ยสูงสุด คือ ผู้นำและภาวะผู้นำ รองลงมา คือ การวัดและประเมินผล วัฒนธรรมองค์กร เทคโนโลยีสารสนเทศ โครงสร้างองค์กร และกลยุทธ์การจัดการความรู้ ตามลำดับ นอกจากนี้ปัจจัยด้านองค์กรมีความสัมพันธ์ต่อกระบวนการจัดการความรู้ของสถาบันทันตกรรมทั้ง 4 กระบวนการ โดยมีความสัมพันธ์เชิงบวกในระดับปานกลาง This research aims to study the level of practice in the knowledge management process, personal factors and the organizational factors related to the knowledge management process of the Institute of Dentistry, the Department of Medical Services in the Ministry of Public Health. The use of the quantitative research method and the data were collected by questionnaire. The samples were included one hundred and twenty four staff at the Institute of Dentistry. The statistics used in data analysis included percentage, mean and standard deviation. The research hypothesizes were to analyze using Pearson’s correlation coefficient. The results revealed the following: 1. Institute of Dentistry practiced the knowledge management process at a moderate level overall. To consider each aspect, all processes were moderately implemented. The highest mean process was using knowledge and the next was transferring knowledge, creating and seeking knowledge and organizing knowledge, respectively. 2. Personnel factors relating to the knowledge management process of Institute of Dentistry was at a high level overall. To consider each aspect, the highest mean factors were achievement motivation and self-learning. The factor of employee empowerment was at a moderate level. There was a positive relationship at a moderate level between the four personnel factors and knowledge management processes at the Institute of Dentistry such as creating and seeking knowledge, organizing knowledge, transiting knowledge and using knowledge. 3. Organizational factors related to the knowledge management process at the Institute of Dentistry was in moderate level overall. In terms of each aspect, it was found that all factors were at a moderate level. The highest mean factor was leaders and leadership. The next was assessment and evaluation, followed by organizational culture, information technology, organizational structure, and knowledge management strategies, respectively. There was a positive relationship at a moderate level between the four personnel factors and knowledge management processes of the Institute of Dentistry.